Field-Induced Slow Magnetic Relaxation in Pentacoordinate Co(II) Complexes: Tuning Magnetic Anisotropy Through Halide Substitution - Hong-Yao Guo; Wei-Quan Lin; Ji-Dong Leng (Molecules)
We report the synthesis, structural characterization, and magnetic properties of three pentacoordinate Co(II) complexes [CoX(dppb)2]X (X = Cl (1Cl), Br (2Br), and I (3I)) supported by the bidentate phosphine ligand 1,2-bis(diphenylphosphino)benzene (dppb). Single-crystal X-ray diffraction reveals that all three complexes adopt similar vacant octahedron (C4v) geometries with the halide ligand in one axial position. Magnetic studies demonstrate that these complexes exhibit field-induced slow magnetic relaxation behaviors, with positive D values of 25.3(2), 21.6(1), and 19.4(2) cm−1 for 1Cl, 2Br, and 3I, respectively. Detailed analysis of the relaxation dynamics reveals that Raman processes dominate at higher temperatures, with systematic variations in relaxation parameters across the series. The systematic variations in magnetic anisotropy and slow magnetic relaxation behaviors of the three complexes correlate with the decreasing electronegativity of the halide ligands.